2005
DOI: 10.2991/jnmp.2005.12.1.2
|View full text |Cite
|
Sign up to set email alerts
|

A Note on the Degasperis-Procesi Equation

Abstract: We prove that smooth solutions of the Degasperis-Procesi equation have infinite propagation speed: they loose instantly the property of having compact support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
49
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 20 publications
(19 reference statements)
0
49
0
Order By: Relevance
“…Lundmark and Szmigielski [15,16] used an inverse scattering approach to determine an explicit formula for the general npeakon solution of the Degasperis-Procesi equation (1.1). Mustafa [17] showed that smooth solutions to (1.1) have the infinite speed of propagation property.…”
Section: Introductionmentioning
confidence: 99%
“…Lundmark and Szmigielski [15,16] used an inverse scattering approach to determine an explicit formula for the general npeakon solution of the Degasperis-Procesi equation (1.1). Mustafa [17] showed that smooth solutions to (1.1) have the infinite speed of propagation property.…”
Section: Introductionmentioning
confidence: 99%
“…Holm and Staley [20] studied stability of solitons and peakons of equation (1.5) numerically. Analogously to the case of the Camassa-Holm equation [5], Henry [18] and Mustafa [27] showed that smooth solutions to equation (1.5) have an infinite speed of propagation.…”
Section: Introductionmentioning
confidence: 99%
“…Matsuno [42] studied multisoliton solutions and their peakon limits. Analogous to the case of the Camassa-Holm equation [10], Henry [32] and Mustafa [44] showed that smooth solutions to Eq. (1.2) have infinite speed of propagation.…”
Section: Introductionmentioning
confidence: 87%